Three primary synchronous malignancies of the uterus, cervix, and fallopian tube: A case report. Issue 24 (June 2018) - Song, Liang; Li, Qingli; Yang, Kaixuan; Yin, Rutie; Wang, Danqing
Abstract: Rationale: Multiple primary malignancies can occur in the same organ or in multiple organs or systems. Likewise, they can occur simultaneously or successively. Based on the timing of the diagnosis, they are classified as multiple synchronous (i.e., concurrent) or metachronous (i.e., successive) primary malignancies. The vast majority of patients have multiple metachronous malignant tumors; multiple synchronous tumors are rare. Patient concerns: A 63-year-old woman presented with the chief complaint of vaginal fluid discharge for 3 months and abdominal pain for 1 month. Diagnoses: The patient was diagnosed with multiple synchronous primary malignancies: 1) endometrial poorly differentiated serous adenocarcinoma, stage IV; 2) poorly differentiated squamous cell carcinoma of the cervix, stage IB1; and 3) left-sided fallopian tube carcinoma in situ. Interventions: After total abdominal hysterectomy, bilateral salpingo-oophorectomy, and comprehensive staging and debulking, the patient was administered eight courses of adjuvant chemotherapy (taxane carboplatin/taxane cisplatin). Outcomes: After chemotherapy completion, the patient has been undergoing regular follow-up examinations; no recurrence has been noted at 18 months. Lessons: It is important to distinguish between multiple synchronous primary malignancies and metastasis of a primary tumor to select the appropriate treatment regimen and to adequately assess the patient's prognosis. When a cancer patient shows clinical manifestations of another tumor, not only metastasis but also the possibility of multiple synchronous primary malignant tumors should be considered. The duration of follow-up in patients with malignant tumors should be extended as much as possible, as the timely detection and treatment of other primary malignant tumors can prolong survival and improve the quality of life.